Case Report: A case of rapamycin-eluting stent for the treatment of refractory stenosis of arteriovenous fistula stenosis - Xiong, Yu; Tu, Bo; Zhang, Minglu; Chen, Bo; Lai, Qiquan; Chen, Jing; Chen, Ling; Wan, Ziming (Frontiers in Cardiovascular Medicine, 2024)
For patients with repeated stenosis of autologous arteriovenous fistula (AVF), percutaneous transluminal angioplasty (PTA) or bare metal stent placement had limited efficacy. Rapamycin was reported to inhibit neointimal hyperplasia and keep blood vessels patent. In this study, we reported a case with refractory stenosis, i.e. a short duration of patency maintenance after each repeated PTA, which was treated by Rapamycin-eluting stent (RES). The RES extended the patency duration from 4-5 months average to 14 months. The stent was used for maintain dialysis for over 30 months. RES may be an effective way for treating refractory stenosis and to salvage the limited vascular resources.